Macrophage Notch1 Participates in LPS-Induced Acute Lung Injury via Regulating CCR5 Expression in Mice - Ruiyu Zhang; Hui Du; Zhi Liu; Yuxi Lei; Huizhi Hu; Junwen Zheng; Pu Yang; Dongchi Zhao (Frontiers in Bioscience-Landmark)
Background: As pivotal immunoregulatory sentinels in pulmonary defense systems, alveolar macrophages (AMs) play dual roles in mediating inflammatory responses and tissue repair processes during various phases of inflammatory cascades. The present investigation focuses on elucidating the regulatory influence of Notch pathway activation within AM populations on the pathophysiological mechanisms underlying acute lung injury (ALI) development. Methods: To investigate the regulatory roles of Notch intracellular domain (NICD) and C-C chemokine receptor type 5 (CCR5) in pulmonary inflammation, an ALI model was established through lipopolysaccharide (LPS) administration. Complementary studies used macrophage-specific Notch1 knockout mice and immortalized bone marrow-derived macrophages (iBMDMs). Molecular profiling of CCR5 and inflammatory mediators was performed through real-time quantitative reverse transcription PCR (qRT-PCR) and immunofluorescence staining. Functional assessments of macrophage migration were carried out using scratch wound healing assays and transwell migration assays. Results: In the LPS-induced ALI model, pulmonary tissues exhibited elevated expression of both NICD and CCR5. Conversely, Notch1 knockout mice attenuated CCR5 expression, reduced macrophage infiltration and downregulated transcription of pro-inflammatory mediators compared to wild-type controls (p < 0.05). Lung injury was milder in the Notch1-deficient mice model compared to wild mice (p < 0.05). In vitro experiments demonstrated that inhibiting the Notch pathway in macrophages reduced CCR5 expression and attenuated CCL5-induced macrophage migration. Conclusion: Notch signaling regulates macrophage infiltration and the inflammatory response by modulating CCR5 expression in ALI induced by LPS.